2003
DOI: 10.1213/01.ane.0000068822.10113.9e
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Experience: Results from a National Survey Suggest Postoperative Pain Continues to Be Undermanaged

Abstract: A survey of 250 US adults who had undergone a recent surgical procedure asked about their postoperative pain experience. Approximately 80% of patients experienced pain after surgery. Of these patients, 86% had moderate, severe, or extreme pain. Additional efforts are required to improve patients' postoperative pain experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
1,149
6
86

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,805 publications
(1,320 citation statements)
references
References 15 publications
26
1,149
6
86
Order By: Relevance
“…Pasien umumnya mengalami nyeri 2-24 jam pertama pascabedah, yaitu ketika pengaruh anastesi sudah hilang, dan pasien sudah keluar dari ruang pemulihan (Apfelbaum, Chen, Mehta, & Gan, 2003& McGrath, 2004.…”
Section: Pendahuluanunclassified
“…Pasien umumnya mengalami nyeri 2-24 jam pertama pascabedah, yaitu ketika pengaruh anastesi sudah hilang, dan pasien sudah keluar dari ruang pemulihan (Apfelbaum, Chen, Mehta, & Gan, 2003& McGrath, 2004.…”
Section: Pendahuluanunclassified
“…Despite progress in pain management, some studies show that postoperative pain is still undertreated (Apfelbaum, Chen, Mehta, & Gan, 2003;Karanikolas & Swarm, 2000). Research findings also demonstrated a high prevalence of unrelieved pain in Chinese patients undergoing surgery (Chung & Lui, 2003;Shen, Sherwood, McNeill, & Li, 2008).…”
Section: Background and Significance Of The Studymentioning
confidence: 99%
“…Despite the designation of pain as "the fifth vital sign" (International Pain Summit, 2011), acute pain remains variably and often sub-optimally managed (Apfelbaum, Chen, Mehta, & Gan, 2003;Duncan et al, 2014). Poor acute pain management can lead to adverse consequences including post-surgical complications and prolonged hospital stays, increasing healthcare costs (Mackintosh, 2007;Sinatra, 2010) and patient suffering (IASP, 2010;Kehlet, Jensen, & Woolf, 2006).…”
Section: Introductionmentioning
confidence: 99%